Compound, electrolyte and application thereof

CN119638747AActive Publication Date: 2025-03-18SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411538251.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-18
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have problems with fast growth of DCR and poor storage performance in the later period of cycle at high temperatures. High-nickel cathode materials such as NCM811 are prone to interface deterioration and particle breakage under high temperature and high pressure, resulting in rapid life decay.

Method used

A compound containing a pyridine parent is used as an electrolyte additive. This compound neutralizes PF5 derived from the decomposition product of LiPF6 through acid-base coordination reaction, stabilizes the decomposition product and quickly forms a stable protective film, reducing the growth of DCR in the later stage of the battery cycle.

Benefits of technology

It improves the high-temperature cycling and high-temperature storage performance of lithium-ion batteries, reduces the growth of DCR in the later stage of battery cycle, and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112121400000031
    Figure BDA0005112121400000031
  • Figure BDA0005112121400000041
    Figure BDA0005112121400000041
  • Figure BDA0005112121400000042
    Figure BDA0005112121400000042
Patent Text Reader

Abstract

The invention discloses a compound, an electrolyte and application thereof. The compound has a structure as shown in a formula I in the specification. The electrolyte comprises an organic solvent, a lithium salt and an additive, the lithium salt comprises LiPF6, and the additive comprises a compound as shown in a formula I. According to the compound disclosed by the invention, pyridine is taken as a parent body, N has weak alkalinity and can moderately inhibit the acidity of an electrolyte and reduce the generation of HF (Hydrogen Fluoride); according to the present invention, the lithium ion battery electrolyte can be used for neutralizing PF5 derived from the decomposition product of LiPF6, stabilizing the decomposition product PF5 and rapidly forming the stable protection film through the acid-base coordination reaction under the certain condition, can ensure the low resistance, can be used for the lithium ion battery electrolyte, can improve the high-temperature cycle performance and the high-temperature storage performance of the battery, and can be used for the lithium ion battery electrolyte, such that the lithium ion battery electrolyte can be used for the lithium ion battery. And the DCR increase in the later period of battery circulation can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and relates to a compound, an electrolyte and applications thereof. Background Art

[0002] Lithium-ion batteries are key enablers of modern technology, not only because they have high energy density (about 240Wh / kg) and high operating voltage (about 3.6V), but also because of their low self-discharge loss and long cycle life, and most importantly, their environmental friendliness. Their performance is crucial for ultra-portable electronic products such as mobile phones, tablets, laptops, smart watches and other digital products. Two other high-potential application areas include electrical energy storage at different capacity levels from home to grid level and power supply for electric vehicles. At present, research on materials for lithium-ion batteries has been going on for several years, with battery performance and safety being the main concerns.

[0003] With the increasing requirements of new energy policies and the market demand for high-performance batteries, how to improve the energy density and safety of batteries has received more and more attention. Nickel-rich cathode materials are key materials for high-energy-density lithium batteries in the next generation of energy storage devices. Among nickel-rich cathode materials, high-nickel ternary cathode materials (such as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O2) has attracted widespread attention from researchers due to its large charge and discharge capacity, working voltage, high life, long cycle life, and low cost. However, compared with positive electrode materials with low Ni content, some defects limit its widespread development in lithium-ion batteries. Taking NCM811 as an example, its shortcomings are listed as follows: (1) Instability of oxygen elements: The oxygen elements in the layered structure of NCM811 are easily precipitated under circulation or high temperature, and oxygen defects produce lattice defects, posing a safety hazard. (2) High surface alkali content: The lithium residual on the surface of NCM811 will react with H2O and CO2 in the air to generate LiOH and Li2CO3. The impurities generated can accelerate the decomposition of the electrolyte to generate HF, and the transition metals in NCM811 are easily dissolved by HF. (3) Structural instability: During the charge and discharge cycle, the insertion and deintercalation of lithium ions causes the lattice to expand or contract, and causes particle rupture. NCM811 changes from a layered structure to a spinel structure, and Ni 4+ It is easily reduced to Ni by gaining electrons 2+ .

[0004] Materials with high nickel content, such as NCM811, have high operating voltages, usually between 4.2V and 4.4V. They are prone to interface degradation, particle breakage, and electrolyte oxidation under high temperature and high pressure, resulting in rapid life decay at high temperatures. At the same time, too fast growth in battery DCR can lead to battery failure. Therefore, from the perspective of electrolytes, it is necessary to develop cathode electrolyte additives that can passivate the cathode interface at high temperatures and form a stable CEI protective film.

[0005] In recent years, from the perspective of improving the battery charging and discharging capacity and cyclability, storage durability, overcharge safety and other performance, a large number of reports on the practical application of electrolyte additives in lithium secondary batteries have been published. CN103022561A discloses an electrolyte that can improve the high-temperature cycle and storage performance of lithium secondary batteries, comprising lithium salts, organic solvents and additives, and the electrolyte also contains a high-temperature film-forming agent, wherein the high-temperature film-forming agent is one or any combination of δ-valerolactone, γ-valerolactone, γ-caprolactone, and ε-caprolactone, and the mass fraction of the high-temperature film-forming agent in the total amount of the electrolyte is 0.5% to 15%. By adding a high-temperature film-forming agent to the lithium secondary battery electrolyte, a passivation film with excellent thermal stability can be formed on the surface of the positive electrode of the lithium secondary battery, the contact interface between the positive electrode and the electrolyte can be improved, and the decomposition reaction of the electrolyte on the positive electrode material at a higher temperature is inhibited, thereby overcoming the shortcomings of the existing lithium secondary batteries in high temperature environments, such as fast loss of use and storage capacity, low recovery rate and fast expansion of battery thickness, thereby improving the high-temperature cycle and storage characteristics of the battery. CN115579523A discloses an electrolyte for improving the cycle and high-temperature storage performance of lithium-ion batteries, the electrolyte comprising electrolyte lithium salt, organic solvent and composite additive, the composite additive comprising fluoroethylene carbonate, propylene sulfite and at least one of compound I and compound II. The invention combines the synergistic effect of the first two additives on the basis of the first two additives, and can improve the cycle performance and high-temperature storage performance of the battery. In particular, for lithium-ion batteries whose negative electrode materials are graphite, a composite material of single crystal silicon and graphite, or a composite material of silicon oxide and graphite, it has high safety, excellent cycle stability and high-temperature storage performance. CN109818064A discloses a high-temperature and high-voltage non-aqueous electrolyte and a lithium-ion battery containing the non-aqueous electrolyte, the high-temperature and high-voltage non-aqueous electrolyte comprises lithium salt, non-aqueous solvent and additive, wherein the additive comprises a first type of borate additive, a second type of nitrogen-containing lithium salt additive, a third type of silicon nitrogen-based additive and a fourth type of sulfonate and sulfate ester mixed additive. By properly mixing various additives, they can not only bring out their respective advantages but also suppress each other's disadvantages. Through their synergistic effect, the high-temperature storage performance of the battery is improved, and the high-temperature cycle performance of the battery is improved. It has good application prospects under high temperature and high voltage conditions.

[0006] However, higher performance electrolyte additives need to be developed urgently to prepare an electrolyte that can combine high temperature cycling and storage performance while ensuring a smaller DCR increase in the later stages of the battery cycle. Summary of the invention

[0007] In view of the above technical problems existing in the prior art, the purpose of the present invention is to propose a compound, an electrolyte and its application. The electrolyte of the present invention can not only improve the high temperature storage performance and high temperature cycle performance of the battery, but also ensure that the DCR growth in the later stage of the battery cycle is small, so that the battery has good comprehensive performance. To achieve the above purpose, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a compound having a structure shown in Formula I:

[0009]

[0010] Wherein, R1-R4 are independently selected from any one of a saturated alkyl group or an unsaturated alkyl group.

[0011] The compound of the present invention uses pyridine as a parent body, wherein N has weak alkalinity and can moderately suppress the acidity of the electrolyte; in combination with phosphate oxygen and saturated or unsaturated alkyl groups, under certain conditions, through acid-base coordination reaction, it can neutralize PF5 derived from the decomposition product of LiPF6, stabilize the decomposition product PF5, quickly form a stable protective film, and at the same time ensure low resistance, and can be used in the electrolyte of lithium-ion batteries, improve the high-temperature cycle performance and high-temperature storage performance of the battery, and can reduce the DCR growth in the later stage of the battery cycle.

[0012] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0013] Preferably, the R1-R4 are linear alkyl groups.

[0014] Preferably, the general formula of the saturated alkyl group is C n H 2n+1 , 1≤n≤3.

[0015] Preferably, the general formula of the unsaturated alkyl group is C n H 2n , 2≤n≤3, the unsaturated alkyl group includes a carbon-carbon double bond.

[0016] Preferably, R1 is the same as R3, and R2 is the same as R4.

[0017] Preferably, R1-R4 are all propenyl.

[0018] In a second aspect, the present invention provides a method for preparing the compound according to the first aspect, the preparation method comprising the following steps:

[0019] I. Synthesis of 2,6-dihydroxypyridine: Raw material a is reacted to obtain product A, and the reaction process is as follows:

[0020]

[0021] II. Synthesis of 2,6-dichloropyridine: Product A is reacted to obtain product B. The reaction process is as follows:

[0022]

[0023]

[0024] III. Synthesis of tetraalkylpyridine-2,6-diyldimethylphosphonate: Product B reacts with raw material b to obtain product C, wherein raw material b is trialkyl phosphite.

[0025] As a preferred technical solution of the preparation method of the present invention, in I, the reaction is carried out in a solvent, and the solvent is anhydrous tetrahydrofuran (THF).

[0026] Preferably, in I, the reaction is carried out in the presence of a catalyst, and the catalyst is preferably lithium aluminum hydride (LiAlH4). Under the action of the catalyst, the carbonyl group in the carboxyl group is reduced to an alkyl group.

[0027] Preferably, 2,6-pyridinedicarboxylic acid is dissolved in anhydrous tetrahydrofuran and cooled. Preferably, the cooling temperature is 0° C. and the cooling time is 10 min to 30 min.

[0028] Preferably, the molar ratio of 2,6-pyridinedicarboxylic acid to lithium aluminum hydride is less than 1:1, for example, it may be 59.8:116.

[0029] Preferably, in I, the reaction is carried out under reflux stirring, and the reflux stirring temperature is 50°C-70°C, for example, it can be 50°C, 52°C, 55°C, 56°C, 58°C, 60°C, 62°C, 63°C, 65°C, 68°C or 70°C, etc.; the reflux stirring time is 18h-30h, for example, it can be 18h, 20h, 21h, 22h, 24h, 25h, 28h or 30h, etc.

[0030] Preferably, before the reflux stirring, room temperature stirring is carried out first, and the stirring time at room temperature is preferably 20 min to 45 min, for example, it can be 20 min, 22 min, 23 min, 24 min, 25 min, 26 min, 28 min, 30 min, 32 min, 33 min, 35 min, 36 min, 37 min, 38 min, 40 min, 43 min or 45 min, etc.

[0031] In the present invention, room temperature refers to 20 to 28°C, for example, it may be 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C or 28°C.

[0032] Preferably, after the reflux stirring, cooling and extraction are performed to obtain a crude product, and the crude product is purified to obtain an intermediate product 2,5-dihydroxypyridine.

[0033] As a preferred technical solution of the preparation method of the present invention, in II, the reaction is carried out in a solvent, and the solvent is dichloromethane (CH2Cl2).

[0034] Preferably, in II, the reaction is carried out in the presence of thionyl chloride (SOCl2).

[0035] Preferably, the molar ratio of the 2,6-dihydroxypyridine to the thionyl chloride is 1:(2-4), for example, it can be 1:2, 1:2.2, 1:2.3, 1:2.4, 1:.2.5, 1:2.7, 1:2.8, 1:3, 1:3.2, 1:3.3, 1:3.5, 1:3.6, 1:3.8 or 1:4, etc.

[0036] Preferably, in II, the reaction is carried out under stirring at room temperature.

[0037] Preferably, in II, the reaction time is 8 h to 12 h, for example, it can be 8 h, 8.2 h, 8.5 h, 8.7 h, 8.8 h, 9 h, 9.3 h, 9.6 h, 9.8 h or 10 h.

[0038] Preferably, in III, the reaction scheme is as follows:

[0039]

[0040] Wherein, R5, R6 and R' are independently selected from any one of a saturated alkyl group or an unsaturated alkyl group;

[0041] As a preferred technical solution of the preparation method of the present invention, in III, the reaction is carried out in a solvent, and the solvent is N,N-dimethylformamide (DMF).

[0042] Preferably, in III, the molar ratio of product B to raw material b is 1 to 1.2, for example, it can be 1, 1.02, 1.05, 1.08, 1.1, 1.12, 1.14, 1.15, 1.16, 1.18 or 1.2, etc.

[0043] Preferably, in III, the reaction is carried out under the protection of a protective gas, and the protective gas comprises at least one of nitrogen, helium and argon.

[0044] Preferably, in III, the reaction temperature is 160°C to 180°C, for example, it can be 160°C, 163°C, 165°C, 167°C, 168°C, 170°C, 172°C, 174°C, 175°C, 177°C or 180°C, etc.; the reaction time is 6h to 8h, for example, it can be 6h, 6.2h, 6.4h, 6.5h, 6.6h, 6.8h, 7h, 7.3h, 7.6h, 7.8h or 8h, etc.

[0045] Preferably, in III, the reaction is followed by extraction and purification.

[0046] In a third aspect, the present invention provides an electrolyte comprising an organic solvent, a lithium salt and an additive, wherein the lithium salt comprises LiPF6, and the additive comprises the compound represented by formula I described in the first aspect.

[0047] LiPF6, a common lithium salt in the electrolyte, is an unstable compound. Side reactions as shown in the following formulas (1) to (5) will occur inside the battery. The decomposition products PF5 and HF of the reactions will react with the components of the SEI and CEI films on the surfaces of the positive and negative electrodes, causing damage to the CEI and SEI films, continuously consuming the electrolyte and affecting battery performance.

[0048] LiPF6 → LiF↓ + PF5 Formula (1)

[0049] HF + ROCOOLi → LiF↓ + ROCOOH Formula (2)

[0050] HF + Li2CO3 → LiF↓ + H2O + CO2↑ Formula (3)

[0051] 2ROCOOLi + PF5 + H2O →2LiF + 2ROCOOH + PF3O Formula (4)

[0052] Li2CO3 + PF5 → 2LiF↓ +PF3O + CO2↑ Formula (5)

[0053] The present invention adds the compound shown in formula I as an additive to the electrolyte. During the pre-charging process, the phosphate oxygen in the additive molecule preferentially participates in the reaction, neutralizes PF5 derived from the decomposition product of LiPF6 through an acid-base coordination reaction, stabilizes the decomposition product PF5, and finally generates a complex covering the electrode surface, quickly forming a stable solid electrolyte interface film (Solid Electrolyte Interphase, CEI film), which can passivate the positive electrode interface and form a stable protective film, thereby avoiding the side reaction of decomposition of the lithium salt LiPF6. At the same time, the amine group in the additive will combine with HF, reducing the influence of HF on the battery. The stable SEI film can also improve the high-temperature cycle performance and high-temperature storage performance of the battery, and can reduce the DCR growth in the late stage of the battery cycle.

[0054] Taking the compound represented by Formula I in which R1-R4 are all propenyl as an example, the specific mechanism of action is explained as follows:

[0055]

[0056] Preferably, the R1-R4 are linear alkyl groups.

[0057] Preferably, the general formula of the saturated alkyl group is C n H 2n+1 , 1≤n≤3.

[0058] Preferably, the general formula of the unsaturated alkyl group is C n H 2n , 2≤n≤3, the unsaturated alkyl group includes a carbon-carbon double bond.

[0059] In the present invention, by limiting the chain length of the saturated alkyl group and the unsaturated alkyl group, the film formation can be better controlled and the impedance can be reduced.

[0060] Preferably, R1 is the same as R3, and R2 is the same as R4.

[0061] Preferably, R1-R4 are all propenyl groups. In this case, due to the presence of propenyl groups, the compound shown in Formula I can be polymerized during the pre-charging process, and the formed CEI film is uniform and thin, covering the surface of the positive and negative electrode materials, improving the stability of the battery under high voltage conditions, improving the battery cycle life and storage life, and reducing the DCR growth in the late cycle.

[0062] As a preferred technical solution of the electrolyte of the present invention, based on the total mass of the electrolyte as 100%, the mass fraction of the compound represented by formula I is 0.01% to 5%, for example, it can be 0.01%, 0.05%, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 0.1% to 2%.

[0063] As a preferred technical solution of the electrolyte of the present invention, the additives also include high-temperature additives.

[0064] Preferably, the high temperature additive includes any one of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, vinyl sulfate, 1,3-propane sultone, tris(trimethylsilyl) borate or tris(trimethylsilyl) phosphate or a combination of at least two thereof, wherein a typical but non-limiting example of the combination is a combination of vinylene carbonate and vinyl ethylene carbonate, a combination of vinyl ethylene carbonate and fluoroethylene carbonate, and a combination of 1,3-propane sultone and tris(trimethylsilyl) borate. 1,3-propane sultone is preferred.

[0065] Preferably, based on the total mass of the electrolyte as 100%, the mass fraction of the high-temperature additive is 0.01% to 2.5%, for example, it can be 0.01%, 0.05%, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2% or 2.5%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 0.1% to 1.5%.

[0066] As a preferred technical solution of the electrolyte of the present invention, the lithium salt mainly includes lithium hexafluorophosphate.

[0067] Preferably, based on the total mass of the electrolyte as 100%, the mass fraction of the lithium hexafluorophosphate is 10% to 15%, for example, it can be 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5% or 15%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0068] Preferably, the lithium salt further includes lithium difluorophosphate and / or lithium bis(fluorosulfonyl)imide.

[0069] Preferably, based on the total mass of the electrolyte as 100%, the mass fraction of the lithium difluorophosphate is 0.5% to 1%, for example, it can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0070] Preferably, based on the total mass of the electrolyte as 100%, the mass fraction of the lithium bis(fluorosulfonyl)imide is 0.1% to 10%, for example, it can be 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9% or 10%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0071] As a preferred technical solution of the electrolyte of the present invention, the organic solvent includes 60-90 cyclic carbonate esters and chain acid esters.

[0072] Preferably, the volume ratio of the cyclic carbonate to the linear acid ester is (10-40):(60-90), wherein the selection range of the cyclic carbonate is "10-40", for example, it can be 10, 12, 14, 15, 16, 18, 20, 23, 25, 26, 28, 30, 32, 34, 35, 36, 38 or 40, etc.; the selection range of the linear acid ester is "60-90", for example, it can be 60, 65, 70, 75, 80, 85 or 90, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably (15-40):(60-85).

[0073] Preferably, the cyclic carbonate comprises any one of ethylene carbonate, propylene carbonate or butylene carbonate or a combination of at least two thereof, wherein typical but non-limiting examples of the combination include: a combination of ethylene carbonate and propylene carbonate, a combination of propylene carbonate and butylene carbonate, etc.

[0074] Preferably, the linear acid ester comprises any one or a combination of at least two of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate or propyl acetate. Wherein, typical but non-limiting examples of the combination include: a combination of dimethyl carbonate and diethyl carbonate, a combination of ethyl methyl carbonate and methyl propyl carbonate, a combination of ethyl propyl carbonate and methyl formate, a combination of methyl formate and ethyl formate, a combination of propyl formate and methyl acetate, a combination of ethyl acetate and propyl acetate, etc. Preferably, it is a combination of ethyl methyl carbonate and dimethyl carbonate.

[0075] Preferably, based on the total mass of the electrolyte as 100%, the mass fraction of the organic solvent is 70% to 85%, for example, it can be 70%, 72%, 73%, 74%, 75%, 76%, 78%, 80%, 82%, 83%, 84% or 85%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0076] The organic solvent in the present invention can better avoid the damage of water to the electrolyte, and at the same time is conducive to promoting the more complete dissolution of the components in the electrolyte, thereby improving the synergy between the components and obtaining an electrolyte with excellent electrochemical properties.

[0077] In a third aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery contains the electrolyte described in the second aspect.

[0078] The lithium-ion battery of the present invention further comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is located between the positive electrode sheet and the negative electrode sheet.

[0079] Preferably, the positive electrode active material in the positive electrode plate includes lithium transition metal oxide and / or lithium transition metal phosphate compound.

[0080] Preferably, the lithium transition metal oxide includes LiCoO2, LiNi x Co y Mn z O2 (0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1), LiNi x Mn y O2 (0≤x≤1, 0≤y≤1, x+y=1), LiMn2O4, LiMnO2 or Li2MnO4, or a combination of at least two thereof. Typical but non-limiting examples of the combination include: LiCoO2 and LiNi x Co y Mn z Combination of O2, LiNi x Mn y O2 and LiMn2O4 combination, LiMnO2 and Li2MnO4 combination, etc. For example, the value of x can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1; the value of y can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1; the value of z can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1, etc., but are not limited to the listed values, and other values ​​not listed in the above ranges are also applicable. It should be noted that LiNi xCo y Mn z O2 and LiNi x Mn y The values ​​of x in O2 can be the same or different. Similarly, the values ​​of y can be the same or different.

[0081] Preferably, the lithium transition metal phosphate compound mainly includes any one of LiFePO4, LiMnPO4 or LiCoPO4 or a combination of at least two thereof. Typical but non-limiting examples of the combination include: a combination of LiFePO4 and LiMnPO4, a combination of LiMnPO4 and LiCoPO4, etc.

[0082] Preferably, the negative electrode active material in the negative electrode plate includes any one of a carbonaceous material, an alloy material, or a metal composite material containing lithium, or a combination of at least two of them. Typical but non-limiting examples of the combination include: a combination of a carbonaceous material and an alloy material, a combination of an alloy material and a metal composite material containing lithium, or a combination of a carbonaceous material and a metal composite material containing lithium.

[0083] Preferably, the negative electrode active material in the negative electrode plate includes any one of natural graphite, artificial graphite, soft carbon, hard carbon, and lithium titanate, or a combination of at least two of them. Typical but non-limiting examples of the combination include: a combination of natural graphite and artificial graphite, a combination of artificial graphite and soft carbon, a combination of soft carbon and hard carbon, a combination of hard carbon and lithium titanate, etc.

[0084] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0085] Compared with the prior art, the present invention has the following beneficial effects:

[0086] The compound of the present invention uses pyridine as a parent body, wherein N has weak alkalinity and can moderately suppress the acidity of the electrolyte; in combination with phosphate oxygen and saturated or unsaturated alkyl groups, under certain conditions, through acid-base coordination reaction, it can neutralize PF5 derived from the decomposition product of LiPF6, stabilize the decomposition product PF5, quickly form a stable protective film, and at the same time ensure low resistance, and can be used in the electrolyte of lithium-ion batteries, improve the high-temperature cycle performance and high-temperature storage performance of the battery, and can reduce the DCR growth in the later stage of the battery cycle. DETAILED DESCRIPTION

[0087] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0088] The compounds of the structures shown in Formula 1-1, Formula 1-2 and Formula 1-3 used in this embodiment are all prepared by the following method, which comprises the following steps:

[0089] 1) 2,6-pyridinedicarboxylic acid (10 g, 59.8 mmol) was dissolved in 800 mL of anhydrous tetrahydrofuran, cooled at 0°C for 20 minutes, and then lithium aluminum hydride LiAlH4 (4.4 g, 116 mmol) was added and stirred at room temperature for 30 minutes. The mixture was heated to 60°C and refluxed for 24 hours. The mixture was then cooled to 0°C and water was added to cool the reaction. The mixture was extracted with ethyl acetate for 5 times, each time with 200 mL of ethyl acetate, dried and concentrated with anhydrous sodium sulfate, and the crude product was purified on a silica gel column with chloroform / ethanol (volume ratio 20:1) as the eluent to obtain the intermediate product 2,5-dihydroxypyridine.

[0090] 2) Dissolve 2,6-dihydroxypyridine (1.44 g, 0.01 mol) in 20 mL of dichloromethane, then slowly add thionyl chloride (3.57 g, 0.03 mol) dropwise under nitrogen protection, stir at room temperature for 10 h, and react to obtain 2,6-dichloromethylpyridine.

[0091] 3) Dissolve 2,6-dichloromethylpyridine (1.74 g, 0.01 mol) and N,N-dimethylformamide (DMF), add trialkyl phosphite (1.36 g, 0.011 mol), stir at 170°C under nitrogen protection for 7 h, treat the excess DMF with distilled water, extract with ethyl acetate, and purify by rotary evaporation on a silica gel column to obtain the final product tetraalkylpyridine-2,6-diyldimethylphosphonate, the mass of the final product is 2.818 g (0.008 mol) (yield: 73.48%).

[0092] The compound prepared by the above method has a structure as shown in Formula I:

[0093]

[0094] Wherein, R1-R4 are independently selected from any one of a saturated alkyl group or an unsaturated alkyl group.

[0095] The raw material trialkyl phosphite in the above preparation method is replaced by trimethyl phosphite, triethyl phosphite and tripropyl phosphite, respectively, to obtain compounds of structures shown in Formula 1-1, Formula 1-2 and Formula 1-3, respectively, and the specific structures are as follows:

[0096]

[0097] Example 1

[0098] This embodiment provides a non-aqueous electrolyte, including a lithium salt, an additive and a solvent, wherein the lithium salt includes lithium hexafluorophosphate and lithium difluorophosphate; the additive includes a compound having a structure shown in Formula 1-1 (tetrapropylene pyridine-2,6-diyl dimethylphosphonate), 1,3-propane sultone and vinyl sulfate; the specific composition of the solvent is: vinyl carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 30:30:40.

[0099] The contents of all the following components are based on the total mass of the non-aqueous electrolyte as 100%, specifically:

[0100] The mass fraction of lithium hexafluorophosphate is 12.5%, and the mass fraction of lithium difluorophosphate is 1%;

[0101] The mass fraction of the compound having the structure shown in Formula 1-1 is 0.5%, the mass fraction of 1,3-propane sultone is 0.5%, and the mass fraction of vinyl sulfate is 1%;

[0102] The mass fraction of the solvent is 84.5%.

[0103] This embodiment also provides a method for preparing the non-aqueous electrolyte, which comprises the following steps:

[0104] When the oxygen content is less than 0.1 ppm and the water content is less than 0.1 ppm, the above components are mixed according to the formula amount and stirred evenly to obtain the non-aqueous electrolyte.

[0105] Example 2

[0106] This embodiment provides a non-aqueous electrolyte, which differs from Embodiment 1 in that the compound having the structure shown in Formula 1-1 is replaced by a compound having the structure shown in Formula 1-2, and the rest is the same as Embodiment 1.

[0107] Example 3

[0108] This embodiment provides a non-aqueous electrolyte. The difference between this embodiment and embodiment 1 is that the contents of all the following components are based on the total mass of the non-aqueous electrolyte as 100%, specifically:

[0109] The mass fraction of lithium hexafluorophosphate is 14%, and the mass fraction of lithium difluorophosphate is 0.4%;

[0110] The mass fraction of the compound having the structure shown in Formula 1-1 is 0.5%, the mass fraction of 1,3-propane sultone is 1%, and the mass fraction of vinyl sulfate is 0.1%;

[0111] The mass fraction of the solvent is 84%.

[0112] The rest are the same as in Example 1.

[0113] Example 4

[0114] This embodiment provides a non-aqueous electrolyte. The difference between this embodiment and embodiment 1 is that the contents of all the following components are based on the total mass of the non-aqueous electrolyte as 100%, specifically:

[0115] The mass fraction of lithium hexafluorophosphate is 11%, and the mass fraction of lithium difluorophosphate is 0.4%;

[0116] The mass fraction of the compound having the structure shown in Formula 1-1 is 0.5%, the mass fraction of 1,3-propane sultone is 1%, and the mass fraction of vinyl sulfate is 1%;

[0117] The mass fraction of the solvent is 86.5%.

[0118] The rest are the same as in Example 1.

[0119] Example 5

[0120] This embodiment provides a non-aqueous electrolyte. The difference between this embodiment and embodiment 1 is that vinyl sulfate is replaced by an equal content of vinylene carbonate, and the rest is the same as embodiment 1.

[0121] Example 6

[0122] The difference between this embodiment and embodiment 1 is that the composition of the solvent is ethylene carbonate and ethyl methyl carbonate in a mass ratio of 3:7, and the rest is the same as embodiment 1.

[0123] Example 7

[0124] This embodiment provides a non-aqueous electrolyte, which differs from Embodiment 1 in that the compound having the structure shown in Formula 1-1 is replaced by a compound having the structure shown in Formula 1-3, and the rest is the same as Embodiment 1.

[0125] Example 8

[0126] The difference between this embodiment and embodiment 1 is that lithium difluorophosphate is replaced by lithium hexafluorophosphate with the same content, and the rest is the same as embodiment 1.

[0127] Example 9

[0128] The difference between this embodiment and embodiment 1 is that 1,3-propane sultone and vinyl sulfate are replaced by equal amounts of a compound having a structure shown in formula 1-2, and the rest is the same as embodiment 1.

[0129] Example 10

[0130] This embodiment provides a non-aqueous electrolyte, including a lithium salt, an additive and a solvent, wherein the lithium salt includes lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide and lithium difluorophosphate; the additive includes a compound having a structure shown in Formula 1-1 (tetrapropylene pyridine-2,6-diyl dimethylphosphonate), 1,3-propane sultone and vinyl sulfate; the specific composition of the solvent is: vinyl carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 30:30:40.

[0131] The contents of all the following components are based on the total mass of the non-aqueous electrolyte as 100%, specifically:

[0132] The mass fraction of lithium hexafluorophosphate is 15%, the mass fraction of lithium bis(fluorosulfonyl)imide is 5%, and the mass fraction of lithium difluorophosphate is 0.7%;

[0133] The mass fraction of the compound having the structure shown in Formula 1-1 is 1.8%, the mass fraction of 1,3-propane sultone is 0.3%, and the mass fraction of vinyl sulfate is 0.2%;

[0134] The mass fraction of the solvent is 77%.

[0135] The rest are the same as in Example 1.

[0136] Embodiment 11

[0137] The difference between this comparative example and Example 1 is that the content of the compound having the structure shown in Formula 1-1 is 3%, and the content of the solvent is adjusted so that the mass fraction of the total system is 100%. The rest is the same as Example 1.

[0138] Comparative Example 1

[0139] The difference between this comparative example and Example 1 is that the compound having the structure shown in Formula 1-1 is not added, and the content of the solvent is adjusted so that the mass fraction of the total system is 100%. The other aspects are the same as Example 1.

[0140] Comparative Example 2

[0141] The difference between this comparative example and Example 1 is that the compound having the structure shown in Formula 1-1 is replaced by an equal amount of fluoroethylene carbonate, and the rest is the same as Example 1.

[0142] Comparative Example 3

[0143] The difference between this comparative example and Example 1 is that the compound having the structure shown in Formula 1-1 is replaced by an equal amount of tris(trimethylsilyl)phosphonate, and the rest is the same as Example 1.

[0144] The electrolytes of Examples 1-11 and Comparative Examples 1-3 are assembled into lithium ion batteries, comprising the following steps:

[0145] (1) Preparation of positive electrode sheets for lithium-ion secondary batteries:

[0146] The positive electrode active material is lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2), conductive agent Super-P, and adhesive PVDF are dissolved in solvent N-methylpyrrolidone at a mass ratio of 95.8:2.2:2.0 and mixed evenly to make positive electrode slurry. The positive electrode slurry is evenly coated on the current collector aluminum foil with a coating amount of 18 mg / cm 2 Then, after drying at 90°C, cold pressing, trimming, cutting, and striping are performed, and then drying is performed at 90°C under vacuum conditions for 4 hours, and the tabs are welded to produce a positive electrode sheet for a lithium-ion secondary battery that meets the requirements.

[0147] (2) Preparation of negative electrode sheets for lithium-ion secondary batteries:

[0148] The negative electrode active material artificial graphite, conductive agent Super-P, thickener CMC, and adhesive SBR were dissolved in solvent deionized water at a mass ratio of 96.5:1.0:1.0:1.5 and mixed evenly to make a negative electrode slurry. The negative electrode slurry was evenly coated on the current collector copper foil with a coating amount of 8.9 mg / cm 2 Then, after drying at 90°C, cold pressing, trimming, cutting, and striping are performed, and then drying is performed at 110°C under vacuum conditions for 4 hours, and the tabs are welded to produce the negative electrode sheet of the lithium-ion secondary battery that meets the requirements.

[0149] (3) Preparation of lithium-ion batteries:

[0150] The positive electrode sheet, negative electrode sheet and isolation film (PE film) of the lithium ion secondary battery prepared according to the above process are made into a battery with a thickness of 8 mm, a width of 60 mm and a length of 130 mm through a lamination process, and are vacuum baked at 90°C for 10 h, injected with the electrolyte in Examples 1-11 and Comparative Examples 1-3, and left to stand for 24 h. Thereafter, the battery is charged to 4.4 V at a constant current of 0.1 C (200 mA), and then charged at a constant voltage of 4.4 V until the current drops to 0.05 C (100 mA), and then discharged to 2.8 V at a constant current of 0.1 C (200 mA), and the charge and discharge are repeated twice. Finally, the battery is charged to 3.8 V at a constant current of 0.1 C (200 mA), and the preparation of the lithium ion secondary battery is completed.

[0151] The prepared lithium ion secondary batteries corresponding to Examples 1-11 and Comparative Examples 1-3 (the lithium ion secondary batteries are numbered as Application Examples 1-11 and Application Comparative Examples 1-3, respectively) were tested for high temperature storage performance, high temperature cycle performance, high temperature cycle discharge DCR growth rate of lithium ion secondary batteries, and high temperature storage gas production performance. The test methods are as follows:

[0152] (1) High temperature storage performance test of lithium-ion secondary batteries:

[0153] At 25°C, the lithium ion secondary battery is first charged to 4.35V at a constant current of 0.05C, further charged to a current of 0.05C at a constant voltage of 4.35V, and then discharged to 2.8V at a constant current of 0.5C. The discharge capacity is the discharge capacity of the lithium ion secondary battery before high-temperature storage; the lithium ion secondary battery is then charged to 4.35V at a constant current of 0.5C, and the lithium ion secondary battery is stored at 60°C for 30 days. After the storage is completed, the lithium ion secondary battery is placed in an environment of 25°C, and then discharged to 2.8V at a constant current of 0.5C. The lithium ion secondary battery is then charged to 4.35V at a constant current of 0.5C, further charged to a current of 0.05C at a constant voltage of 4.35V, and then discharged to 2.8V at a constant current of 0.5C. The last discharge capacity is the discharge capacity of the lithium ion secondary battery after high-temperature storage. Capacity retention rate of lithium ion secondary battery after high temperature storage (%)=[discharge capacity of lithium ion secondary battery after high temperature storage / discharge capacity of lithium ion secondary battery before high temperature storage]×100%.

[0154] (2) High temperature cycle performance test of lithium-ion secondary batteries:

[0155] The high temperature cycle performance of the prepared lithium ion secondary battery was tested respectively. The specific method is: at 45°C, the lithium ion secondary battery was first charged to 4.35V at a constant current of 0.5C, then charged at a constant voltage of 4.35V until the current was cut off at 0.05C, and then discharged to 2.8V at a constant current of 0.5C. This is a charge and discharge cycle process, and the discharge capacity this time is the discharge capacity of the first cycle. The lithium ion secondary battery was subjected to a cyclic charge and discharge test in the above manner, and the discharge capacity of the 1000th cycle was taken. The capacity retention rate (%) of the lithium ion secondary battery after 1000 cycles = [discharge capacity of the 1000th cycle / discharge capacity of the first cycle] × 100%.

[0156] (3) High temperature cycle discharge DCR growth rate test of lithium-ion secondary batteries:

[0157] The high temperature cycle performance of the prepared lithium ion secondary battery was tested respectively. The specific method is as follows: at 45°C, the lithium ion secondary battery was first charged to 4.35V at a constant current of 0.5C, then charged at a constant voltage of 4.35V until the current was cut off at 0.05C, and then discharged at a constant current of 0.5C for 1h to 50% SOC. At 50% SOC, 1C was discharged for 30s, and the voltage before and after discharge was recorded. The voltage was divided by the current of the discharge process to obtain the DCR in this discharge process. The discharge DCR of this time is the discharge DCR before the cycle. The lithium ion secondary battery was subjected to a cyclic charge and discharge test in the above manner, and the battery after the 1000th cycle was taken. The discharge DCR growth rate (%) of the lithium ion secondary battery after 1000 cycles = [discharge DCR of the 1000th cycle / discharge DCR growth before the cycle] × 100% - 100%.

[0158] (4) High temperature storage gas production performance test of lithium-ion secondary batteries:

[0159] At 25°C, the prepared lithium-ion secondary batteries were first charged to 4.35V at a constant current of 0.5C, and then charged to 0.05C at a constant voltage of 4.35V, and then discharged to 2.8V at a constant current of 0.5C. The discharge capacity was the discharge capacity of the lithium-ion secondary battery before high-temperature storage. Then, the lithium-ion secondary battery was charged to 4.35V at a constant current of 0.5C, and charged to 0.05C at a constant voltage of 4.35V, and the lithium-ion battery was fully charged. The volume of the battery was tested by the drainage method, and the thickness of the battery was measured by a micrometer.

[0160] Then the lithium-ion battery was stored at 60°C for 90 days. After the storage, the lithium-ion secondary battery was placed in a 25°C environment and the volume of the battery was tested by the drainage method. Specifically, the beaker filled with pure water was first placed on the balance, weighed, and recorded as reading 1. Then the battery before storage (fresh battery) or the battery after storage was immersed in the water in the beaker, weighed, and recorded as reading 2. The reading 2 minus the reading 1 is the volume of the battery before storage (fresh battery) or the battery after storage. The density of water is 1 mg / mL, and the reading 1mL corresponds to the volume of the battery before storage (fresh battery) or the battery after storage is 1mL. Therefore, the battery immersed in water is before storage, so the reading 2 minus the reading 1 is the volume of the battery before storage; the battery immersed in water is after storage, so the reading 2 minus the reading 1 is the volume of the battery after storage. The volume after storage / the volume before storage is the ratio of the volume of the battery after storage to the volume of the battery before storage. Use a micrometer to measure the thickness of the battery. Then the lithium ion secondary battery is discharged to 2.8V at a constant current of 0.5C, then charged to 4.35V at a constant current of 0.5C, further charged to a current of 0.05C at a constant voltage of 4.35V, and then discharged to 2.8V at a constant current of 0.5C. The last discharge capacity is the discharge capacity of the lithium ion secondary battery after high temperature storage. Battery volume expansion rate (%) = (volume after storage / volume before storage-1) × 100%.

[0161] The test results are shown in Table 1:

[0162] Table 1 Lithium-ion battery performance test results corresponding to different electrolytes

[0163]

[0164] It can be seen from the above table that, compared with comparative example 1), with the addition of the compound having the structure shown in Formula 1-1, Formula 1-2 or Formula 1-3, the capacity retention rate of the lithium-ion secondary battery stored at 60°C increases, the storage gas production decreases, the 45°C high-temperature cycle capacity retention rate increases, and the DCR growth in the later stage of the cycle is also lower, which is beneficial to improving the battery life.

[0165] At the same time, through the comparison of Example 1, Example 2 and Example 7, it can be seen that the compound having the structure shown in Formula 1-3 has a more obvious improvement in battery performance than the compounds having the structures shown in Formula 1-1 and Formula 1-2. This is mainly because: due to the presence of propylene groups, the compound shown in Formula I can be polymerized during the pre-charging process, and the formed CEI film is uniform and thin, covering the surface of the positive and negative electrode materials, thereby improving the stability of the battery under high voltage conditions, improving the battery cycle life and storage life, and reducing the DCR growth in the late cycle.

[0166] By comparing Example 1 with Example 6, it can be seen that since the content of dimethyl carbonate with low viscosity and high conductivity in Example 1 is higher, it is more conducive to improving the performance of the battery.

[0167] By comparing Example 1 with Example 8, it can be seen that in the electrolyte system of the present invention, the compounding of lithium hexafluorophosphate and lithium difluorophosphate is more conducive to improving the performance of the battery than single lithium hexafluorophosphate.

[0168] By comparing Example 1 with Example 9, it can be seen that the use of combined additives is beneficial to battery performance.

[0169] By comparing Example 1 with Example 11, it can be seen that the addition amount of the new additive represented by Formula I (tetraalkylpyridine-2,6-diyldimethylphosphonate) used in this patent is preferably within 2%. Too much addition will increase the battery impedance and affect the battery performance.

[0170] By comparing Example 1 with Comparative Example 2, it can be seen that the new additive tetraalkylpyridine-2,6-diyldimethylphosphonate used in this patent is superior to the traditional additive fluoroethylene carbonate in improving battery performance.

[0171] By comparing Example 1 with Comparative Example 3, it can be seen that the new additive tetraalkylpyridine-2,6-diyldimethylphosphonate used in this patent is superior to the traditional additive tris(trimethylsilane)phosphonate in improving battery performance.

[0172] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A compound, characterized in that The compound has the structure shown in Formula I: Wherein, R1-R4 are independently selected from any one of a saturated alkyl group or an unsaturated alkyl group.

2. The compound according to claim 1, characterized in that The R1-R4 are linear alkyl groups; Preferably, the general formula of the saturated alkyl group is C n H 2n+1 , 1≤n≤3; Preferably, the general formula of the unsaturated alkyl group is C n H 2n , 2≤n≤3, the unsaturated alkyl group includes a carbon-carbon double bond; Preferably, R1 is the same as R3, and R2 is the same as R4; Preferably, R1-R4 are all propenyl.

3. A method for preparing the compound according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: I. Synthesis of 2,6-dihydroxypyridine: Raw material a is reacted to obtain product A, and the reaction process is as follows: II. Synthesis of 2,6-dichloropyridine: Product A is reacted to obtain product B. The reaction process is as follows: III. Synthesis of tetraalkylpyridine-2,6-diyldimethylphosphonate: Product B reacts with raw material b to obtain product C, wherein raw material b is trialkyl phosphite.

4. The preparation method according to claim 3, characterized in that: In 1, the reaction is carried out in a solvent, and the solvent is anhydrous tetrahydrofuran; Preferably, in I, the reaction is carried out in the presence of a catalyst, and the catalyst is preferably lithium aluminum hydride; Preferably, 2,6-pyridinedicarboxylic acid is dissolved in anhydrous tetrahydrofuran and cooled; Preferably, in I, the reaction is carried out under reflux stirring, the reflux stirring temperature is 50°C to 70°C, and the reflux stirring time is 18h to 30h; Preferably, before the reflux stirring, stirring at room temperature is first performed, and the stirring time at room temperature is preferably 20 min to 45 min; Preferably, after the reflux stirring, cooling and extraction are performed to obtain a crude product, and the crude product is purified to obtain an intermediate product 2,5-dihydroxypyridine; Preferably, in II, the reaction is carried out in a solvent, and the solvent is dichloromethane; Preferably, in II, the reaction is carried out in the presence of thionyl chloride; Preferably, the molar ratio of the 2,6-dihydroxypyridine to the thionyl chloride is 1:(2-4); Preferably, in II, the reaction is carried out under stirring at room temperature; Preferably, in II, the reaction time is 8h to 12h; Preferably, in III, the reaction scheme is as follows: Wherein, R5, R6 and R' are independently selected from any one of a saturated alkyl group or an unsaturated alkyl group; Preferably, in III, the reaction is carried out in a solvent, and the solvent is N,N-dimethylformamide; Preferably, in III, the molar ratio of product B to raw material b is 1 to 1.2; Preferably, in III, the reaction is carried out under the protection of a protective gas, and the protective gas comprises at least one of nitrogen, helium and argon; Preferably, in III, the reaction temperature is 160°C to 180°C, and the reaction time is 6h to 8h; Preferably, in III, the reaction is followed by extraction and purification.

5. An electrolyte, characterized in that: The electrolyte includes an organic solvent, a lithium salt and an additive, wherein the lithium salt includes LiPF6, and the additive includes the compound shown in formula I according to claim 1 or 2.

6. The electrolyte according to claim 5, characterized in that Based on the total mass of the electrolyte being 100%, the mass fraction of the compound represented by formula I is 0.01% to 5%, preferably 0.1% to 2%; Preferably, in Formula I, R1-R4 are linear alkyl groups; Preferably, in Formula I, the general formula of the saturated alkyl group is C n H 2n+1 , 1≤n≤3; Preferably, in Formula I, the general formula of the unsaturated alkyl group is C n H 2n , 2≤n≤3, the unsaturated alkyl group includes a carbon-carbon double bond; Preferably, in Formula I, R1 is the same as R3, and R2 is the same as R4; Preferably, in formula I, R1-R4 are all propenyl.

7. The electrolyte according to claim 5 or 6, characterized in that The additives also include high temperature additives; Preferably, the high temperature additive comprises any one or a combination of at least two of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, vinyl sulfate, 1,3-propane sultone, tris(trimethylsilyl)borate or tris(trimethylsilyl)phosphate, preferably 1,3-propane sultone; Preferably, based on the total mass of the electrolyte being 100%, the mass fraction of the high temperature additive is 0.01% to 2.5%, preferably 0.1% to 1.5%.

8. The electrolyte according to any one of claims 5 to 7, characterized in that: The lithium salt mainly includes lithium hexafluorophosphate; Preferably, based on the total mass of the electrolyte being 100%, the mass fraction of the lithium hexafluorophosphate is 10% to 15%; Preferably, the lithium salt further comprises lithium difluorophosphate and / or lithium bis(fluorosulfonyl)imide; Preferably, based on the total mass of the electrolyte being 100%, the mass fraction of the lithium difluorophosphate is 0.5% to 1%; Preferably, based on the total mass of the electrolyte being 100%, the mass fraction of the lithium bis(fluorosulfonyl)imide is 0.1% to 10%.

9. The electrolyte according to any one of claims 5 to 8, characterized in that: The organic solvent includes cyclic carbonate and chain acid ester; Preferably, the volume ratio of the cyclic carbonate and the linear acid ester is (10-40):(60-90), preferably (15-40):(60-85); Preferably, the cyclic carbonate includes any one of ethylene carbonate, propylene carbonate or butylene carbonate or a combination of at least two thereof; Preferably, the linear acid ester includes any one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate or propyl acetate, or a combination of at least two thereof, preferably a combination of ethyl methyl carbonate and dimethyl carbonate; Preferably, based on the total mass of the electrolyte being 100%, the mass fraction of the organic solvent is 70% to 85%.

10. A lithium ion battery, characterized in that: The lithium ion battery contains the electrolyte according to any one of claims 1 to 7; Preferably, the lithium-ion battery further comprises a positive electrode sheet, a negative electrode sheet and a separator, and the separator is located between the positive electrode sheet and the negative electrode sheet; Preferably, the positive electrode active material in the positive electrode plate includes lithium transition metal oxide and / or lithium transition metal phosphate compound; Preferably, the negative electrode active material in the negative electrode plate includes any one of a carbonaceous material, an alloy material or a metal composite material containing lithium, or a combination of at least two of them.

Citation Information

Patent Citations

  • Electrolyte solution capable of improving high temperature cycling and storing performances of lithium secondary battery

    CN103022561A

  • High-temperature high-voltage non-aqueous electrolyte and lithium ion battery containing non-aqueous electrolyte

    CN109818064A

  • Electrolyte for improving cycle and high-temperature storage performance of lithium ion battery

    CN115579523A

  • Non-aqueous electrolyte and lithium ion battery

    CN111082139A

  • Flame-retardant lithium ion battery electrolyte and lithium ion battery containing same

    CN112186244A